Case report: Primary pleural squamous cell carcinoma in a 68-year-old male - Zhong, Chuan; Zhou, Haining; Rami-Porta, Ramón; Zhao, Yunfei (Frontiers in Surgery, 2022)
Introduction: Primary pleural squamous cell carcinoma (PPSCC) is a sporadic disease that is rarely reported in literature. Due to its low incidence, the pathogenesis of PPSCC is unknown. Case summary: We report a case of a 68-year-old male with PPSCC and sizable pulmonary bullae. Two months after complete resection of both lesions, a total dose of 50Gy radiotherapy was administered over the operative field. After more than a year of follow-up, the patient is in steady condition without any sign of recurrence. Conclusions: Since PPSCC is rarely reported, our case proposed that complete surgical resection combined with radiotherapy may be a promising therapeutic approach.